Microstructural and Dielectric Properties of Zr Doped Microwave Sintered CaCu3Ti4O12 Synthesized by Sol-Gel Route. (10th April 2014) - Jesurani, S.; Kanagesan, S.; Hashim, M.; Ismail, I.; Ibrahim, I. R.
Abstract : Polycrystalline samples with the chemical formula CaCu3 Ti 4 - x Zr x O12 (x = 0, 0.02, 0.1, 0.2, 0.5, and 0.1) CCTZO were synthesized from metal nitrate solutions by the sol-gel method, followed by conventional and microwave heat treatments. The X-ray diffraction pattern of powder calcined at 800°C in conventional furnace for 3 h showed formation of a single phase. The crystal structure did not change on doping with zirconium and it remained cubic in the five studied compositions. The surface morphology of samples sintered at 1000°C in microwave furnace for 10 min was observed using a high resolution scanning electron microscope (HR-SEM). The grain sizes were in the range of 250 nm–5 μ m for these samples. HRSEM results show that doping with Zr enhanced grain growth or densification. Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of Zr. The dielectric characteristics of Zr doped CCTO were studied with an LCR meter in the frequency range of 50 Hz–1 MHz. A very high dielectric constant 21, 500 was observed for the sample doped with Zr (0.02 mol%) at 50 Hz.